2016
DOI: 10.1016/j.jpowsour.2016.09.090
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study on the discharge product of Pt-based lithium oxygen batteries

Abstract: Lithium oxygen batteries have attracted much attention due to the high theoretical energy density. However, they suffer a large overpotential during oxygen evolution process and thus catalysts play a vital role in the reaction. Here, we systematically explored the influence of Pt-based nanoparticle catalysts on the discharge product Li 2 O 2. Because of the superior electrical conductivity and the strong binding with oxygen, Pt-based nanoparticles serve as active sites which are favorable for the growth of tor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…6(e) that the VACNF-PtRu maintained a high discharge capacity (> 0.4 mAh•cm −2 ) in its 28 th cycle as compared to other cathodes (< 0.15 mAh•cm −2 ). This superior performance of PtRu catalyst was also reported in previous studies [30].…”
Section: Cycling Stability Testssupporting
confidence: 88%
See 1 more Smart Citation
“…6(e) that the VACNF-PtRu maintained a high discharge capacity (> 0.4 mAh•cm −2 ) in its 28 th cycle as compared to other cathodes (< 0.15 mAh•cm −2 ). This superior performance of PtRu catalyst was also reported in previous studies [30].…”
Section: Cycling Stability Testssupporting
confidence: 88%
“…Ko et al reported the performance of various combinations of noble metal alloys, including Pt-Ru, Pd-Ir, and Pt-Pd supported on Vulcan XC and showed that Pt-Ru/C exhibited highest discharge capacity (346 mAh•g −1 ) followed by Pt-Pd (153 mAh•g −1 ) and Pd-Ir (135 mAh•g −1 ) at a current density of 0.2 mA•cm −2 [30]. Wu et al compared the LOB performance by employing pure Pt and Pt-Ru catalysts supported on Vulcan XC.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Song et al reported that the solid discharge product grows on the Co 3+ -exposed {112} facet of a Co 3 O 4 plate in a unique angular, conical morphology; growth on this facet is preferential over that on the carbon or Co 2+ -exposed {001} facet of Co 3 O 4 cubes . However, compared to prior studies of a Pt-based catalyst in a Li–O 2 battery, a morphologically tailored catalyst with proper surface atomic arrangement on the Pt-based catalysts is unprecedented. In this regard, the purpose of this work is to address the advantage of using an optimized atomic arrangement resulting from morphological characteristics to create a new breakthrough. Herein, we introduce the facile synthesis of anisotropic Pt catalysts, where the catalytic surfaces were exposed with high-index {411} facets along with several low-index facets to maximize the catalytic properties for the ORR/OER in the cathode of Li–O 2 batteries.…”
Section: Introductionmentioning
confidence: 99%
“…As a noble metal element, platinum (Pt) is a frequently used catalytic material with good conductivity, thermal conductivity, and extremely stable chemical properties. 138,139 To date, there have been many investigations on this. 118,140–142 For instance, Lee et al 118 successfully prepared Pt SACs supported on titanium nitride nanoparticles with the aid of chlorine ligands, which showed excellent performance in oxygen reduction, formic acid oxidation as well as methanol oxidation.…”
Section: Typical Sacs Applied In Lobsmentioning
confidence: 99%